Kontribusi Masa Kerja, Disiplin Kerja Dan Supervisi Kepala Sekolah Terhadap Profesionalisme Guru SD Se Kapanewon Moyudan Sleman - Agung Prabowo, Agung Prabowo; Supriyoko, Supriyoko (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to analyze the contribution of working period, working discipline and school principal supervision on the professionalism of Elementary School teachers in Moyudan Sleman Region both simultaneously and partially. This research was conducted at Elementary Schools in Moyudan Sleman Region. This research is quantitative research. The population of this research is all teachers at Elementary Schools in Moyudan Sleman Region amount 187 teachers. To test the validity of this research, it uses product moment correlation (to measure the correlation between different product satisfaction measures) and reliability testing (to measure the consistency of different product satisfaction measures). The hypothesis testing uses multiple regression analysis. The results of this research were obtained together that there was a positive and significant effect of working period, working discipline and school principal supervision on the professionalism of Elementary School Teachers in Moyudan Sleman Region. There was a significant positive effect of working period on the professionalism of Elementary School Teachers in Moyudan Sleman Region. There was a significant positive effect of working discipline on the Professionalism of Elementary School Teachers in Kapanewon Moyudan Sleman Region. There was a significant positive effect of school principal supervision on the Professionalism of Elementary School Teachers in Moyudan Sleman Region.